Handbook of cancer control and behavioral science a resource for researchers, practitioners, and policymakers - Miller, Suzanne M. (American Psychological Association, 2009)
This text is a synthesis of what is known, what is suspected, and what is still unknown about core behavioural and sociocultural aspects of cancer control.